2020
DOI: 10.3390/nu12082357
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Quality of Life in Hospitalised Cancer Patients Who Develop Intestinal Failure and Require Parenteral Nutrition: An Observational Study

Abstract: (1) Background: Malnutrition in cancer patients impacts quality of life (QoL) and performance status (PS). When oral/enteral nutrition is not possible and patients develop intestinal failure, parenteral nutrition (PN) is indicated. Our aim was to assess nutritional status, QoL, and PS in hospitalised cancer patients recently initiated on PN for intestinal failure. (2) Methods: The design was a cross-sectional observational study. The following information was captured: demographic, anthropometric, biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
1
5
0
1
Order By: Relevance
“…In the two papers enrolled in this Systematic Review, nutritional supplementation showed an increase in patient function. In line with this, the same results were obtained also in other neoplasm-affected patients [ 38 , 39 ], demonstrating that better nutritional status is related to better functional capacity and physical resistance to therapies.…”
Section: Discussionsupporting
confidence: 80%
“…In the two papers enrolled in this Systematic Review, nutritional supplementation showed an increase in patient function. In line with this, the same results were obtained also in other neoplasm-affected patients [ 38 , 39 ], demonstrating that better nutritional status is related to better functional capacity and physical resistance to therapies.…”
Section: Discussionsupporting
confidence: 80%
“…Involuntary weight loss is also common in patients with gastrointestinal cancer and is more likely to lose weight in advanced cancer patients (Ravasco et al, 2006). Similarly, up to 87.7% of patients in this study experienced weight loss, which may be related to severe muscle mass depletion caused by advanced cancer (Plyta et al, 2020). In addition, the absence of weight loss accounted for 10.25% (95%CI: 3.04 to 17.47) of the patients' healthy quality of life.…”
Section: Discussionmentioning
confidence: 57%
“…Although only 25.9% of the patients in this study had low self‐care ability, the study found that when the patient's self‐care ability was high, it could still be used as an independent factor to increase the likelihood of developing a healthy quality of life (95% CI: 32.16 to 75.61), which may be related to the fact that self‐care ability represents the degree of individual independence and activity to some extent. It is an important index of patients' physical status and daily activity ability (Plyta et al, 2020; Yates et al, 1980). Plyta et al (2020) explored the relationship between nutritional status and quality of life of hospitalized cancer patients with intestinal failure and need parenteral nutrition and found that KPS, which is impaired by muscle strength, was the main component of QoL damage in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grupo total Idosas Adultas ...continuação -Tabela 3 não é recomendado para avaliar desnutrição em oncologia, uma vez que não consegue diferenciar com precisão os componentes do peso corporal, podendo mascarar a perda de massa magra em pessoas com IMC dentro da faixa saudável ou com excesso de peso 21,22 . O que torna importante a utilização de outros métodos de avaliação como a ASG-PPP que possui maior sensibilidade em pacientes com câncer 23,24 . Santos et al 25 ao avaliarem 366 pacientes com câncer, observaram em amostra de 32 mulheres com câncer ginecológico, percentual de desnutrição em torno de 44% através da ASG-PPP.…”
Section: Faixa Etáriaunclassified